How languages saved me : a Polish story of survival - Haska, Tadeusz Leon; Naumann, Stefanie (2019)
"Orphaned in Poland at the age of thirteen, Tadeusz "Tad" Haska survived World War II on the run, narrowly evading the Nazis every step of the way. After the war, he daringly escaped jail by the Soviet Secret Police, fled to Sweden and launched an elaborate plan to smuggle his wife in a coffin on an all-male naval ship. Discover how Tad's knowledge of nine languages helped him survive in the face of unspeakable adversity."–Amazon.com